Labour, Social Inequalities and Trade Unionism - Estanque, Elísio (2009)
In recent years, the world of labour has been affected by a vast array of changes in the context of the global economy in which we live and as a result of the effects of several transnational forces and institutions. Resorting to examples from recent empirical studies carried out by the author, this article analyses and discusses the ongoing processes of change, taking as a starting point issues related to the world of labour and connecting them with the broader issue of inequality and social classes. The main aim is to make a diagnosis and a critical interpretation of some of these changes in Portuguese society, showing their relevance, significance and implications for trade unionism. Thus, after a critical reflection on the new lines of labour market segmentation and social inequality, the author points to a set of questions concerning trade unionism, offering points for further reflection and critical analysis of the experiences and problems with which it is engaged.